Plasma YKL-40: A BMI-Independent Marker of Type 2 Diabetes - Nielsen, Anders R. (American Diabetes Association, 2008)
OBJECTIVE—YKL-40 is produced by macrophages, and plasma YKL-40 is elevated in patients with diseases characterized by inflammation. In the present study, YKL-40 was examined in relation to obesity, inflammation, and type 2 diabetes. RESEARCH DESIGN AND METHODS—Plasma YKL-40 and adipose tissue YKL-40 mRNA levels were investigated in 199 subjects who were divided into four groups depending on the presence or absence of type 2 diabetes and obesity. In addition, plasma YKL-40 was examined in healthy subjects during a hyperglycemic clamp, in which the plasma glucose level was kept at 15 mmol/l for 3 h, and during a hyperinsulinemic-euglycemic clamp. RESULTS—Patients with type 2 diabetes had higher plasma YKL-40 (76.7 vs. 45.1 ng/ml, P = 0.0001) but not higher expression in adipose tissue YKL-40 mRNA (1.20 vs. 0.98, P = 0.2) compared with subjects with a normal glucose tolerance. Within the groups with normal glucose tolerance and type 2 diabetes, obesity subgroups showed no difference with respect to either plasma YKL-40 or adipose tissue YKL-40 mRNA levels. Multivariate regression analysis showed that plasma YKL-40 was associated with fasting plasma glucose (β = 0.5, P = 0.0014) and plasma interleukin (IL)-6 (β = 0.2, P = 0.0303). Plasma YKL-40 was not related to parameters of obesity. There were no changes in plasma YKL-40 in healthy subjects during either hyperglycemic or hyperinsulinemic-euglycemic clamps. CONCLUSIONS—Plasma YKL-40 was identified as an obesity-independent marker of type 2 diabetes related to fasting plasma glucose and plasma IL-6 levels.